Important Features of Certain Words in English and Uzbek and their Use - Budikova Marguba Xoshimovna (Scientific Trends, 2023)
Choosing the concept of "property" as the subject of linguistic research, we could not leave out phraseological units and paremies in English and Uzbek, which are important for creating a holistic image of the object under consideration.
Keywords: concept, phraseological units, paremiological units.